Metrics and Altmetrics: an exploratory study of a possible correlation between the most cited papers in open and restricted access in 2016-2018 - Pacheco, André (2018)
Citations count in reference databases has been consolidated as the traditional method of assessing the impact of a scientific work. However, the recent developments around the diversity of web communication channels triggered the scientific community to start questioning the legitimacy of these metrics as the sole indicators of impact. In this context, alternative metrics based on web indicators have begun to emerge. This study attempts to determine the existence of a correlation between traditional citations and altmetric mentions, while also considering if the type of access — open or restricted — has an influence in the impact of a publication. The study is based on a mixed methodology. The sample was composed by the most cited hot papers extracted from the Web of Science, and the most mentioned papers in Altmetrics, between 2016 and 2018, according to type of access. Their numbers in altmetrics and in reference databases (Web of Science and Scopus) was collected and the data was analyzed using Spearman’s correlation coefficient. It is concluded that there is not a significant correlation between citations and altmetrics mentions, and that the type of access is not relevant for a paper’s success.